The Roots of Atractylodes macrocephala Koidzumi Enhanced Glucose and Lipid Metabolism in C2C12 Myotubes via Mitochondrial Regulation - Song, Mi Young (Evid Based Complement Alternat Med, 2015)
The root of Atractylodes macrocephala Koidzumi (Atractylodis Rhizoma Alba, ARA) is a Traditional Korean Medicine and has been commonly used for weight control. Mitochondrial dysfunction appears to be a key contributor to insulin resistance, and therefore mitochondrial targeting drugs represent an important potential strategy for the treatment of insulin resistance and obesity. In this study, the authors investigated the regulatory effects of ARA on mitochondrial function with respect to the stimulation of glucose and lipid metabolism in C2C12 myotubes. After differentiating C2C12 myotubes, cells were treated with or without different concentrations (0.2, 0.5, and 1.0 mg/mL) of ARA extract. ARA extract significantly increased the expression of peroxisome proliferator-activated receptor coactivator 1 alpha (PGC1α) and the downregulations of its targets, nuclear respiratory factor-1 (NRF-1), transcription factor A (TFAM), and total ATP content in C2C12 myotubes. ARA extract also increased the expressions of PGC1α activator and of the metabolic sensors, AMP-activated protein kinase (AMPK), and acetyl-CoA carboxylase and sirtuin (SIRT) 1. Furthermore, it significantly increased glucose uptake by enhancing glucose consumption and subsequently decreased FFA contents and increased carnitine palmitoyltransferase (CPT) 1b expression. Our study indicates that ARA has a potential for stimulating mitochondrial function and energy metabolism in muscle.